Kos in the Neolithic and early Bronze Age : the Halasarna finds and the Aegean settlement pattern - Georgiadis, Mercourios (Prehistory monographs, 2012)
12Early Bronze Age Settlement Patterns13 Diachronic Developments in the Halasarna Region in TheirBroader Aegean Context; References; Index.